Influence of the Flange Connection and the Stresses Arising in It on the Life Indices of the Intermediate-Pressure Cylinder of К-200-130 Turbine - Chernousenko, Olga Yuryevna; Peshko, Vitaliy Anatoliyovich (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2016)
It is proposed to improve the model of the casing for the intermediate pressure cylinder of the К-200-130 turbine by making the structural type of the flanges of horizontal connector similar to the real type, taking into consideration the stresses that arise in doweled joints. It was shown that the transition from the model with the flanges of a simplified type to the model of a real type is accompanied both by the total decrease in the intensity of stresses inside the casing at all hot starts and the appearance of new stress concentrators on the outer part in the places of transition from the flanges to thin-wall casing elements. The registration of stresses that arise in the flanges showed a considerable influence of pin tightening on the mode of deformation of the turbine casing. These stresses compensate to some extent the stresses caused by pressure and temperature field differences and contribute to the improvement of the life indices of the casing, in particular the acceptable number of all hot starts, cyclic and statistical failures, and the residual life of the IPC casings of the К-200-130 turbine.